EFFECT OF ASTAXANTHIN ON THE COLOR INTENSITY OF GUPPY FISH (Poecilia reticulata) - petrus soedibya; Abidzar Hawari; Kasprijo Kasprijo; Sri Marnani; Muslih Muslih; Ren Fitriadi (Journal Of Artha Biological Engineering, 2024)
Guppy fish is one type of ornamental fish which is in great demand due to its interesting color variations. Color of ornamental fish will be brighter if the feed contains color pigments. The study aims to determine the effect of Astaxanthin supplement in pellets on the color brightness of guppies and to find the best dose of Astaxanthin supplement in pellets on the color brightness of guppies. The method used in the study was complete randomized design (CRD) consisting of five treatments (Astaxanthin supplements of 0%, 2%, 3%, 4% and 5%) and three replications. The experimental fish were male guppy fish Strain HB Red ± 3 cm length with a density of 3 fish/aquarium. Feeding was done twice a day and siphoning was done every afternoon. The parameters observed were Chroma value, survival rate and water quality. The results show that the supplement of Astaxanthin in pellets successfully increase the brightness of guppies and the best dose of Astaxanthin supplement in pellets was 5% with an increase in Chroma value of 4.82%. The survival rate obtained was 100%. Water quality includes an average temperature of 26-27 ℃ and pH of 6-7 and dissolved oxygen (DO) was 6.95-7.93 ppm